Accounting Subject Achievement of 11th Grade Social Students at SMA Murni Bandar Baru was Influenced by Family and School Environment - Arfan Ikhsan; Indra Maipita; Higinus Bonaventura Salu (Randwick International of Education and Linguistics Science Journal, 2024)
This research was carried out at SMA Deli Murni Bandar Baru with the aim of describing the students' family and school environments as well as describing students' academic achievements in accounting subjects and knowing the influence of the family and school environment on students' academic achievements in accounting subjects. This research used a descriptive verification approach with a sample size of 110 students from a total population of 148. The population consisted of 11th grade of IPS (Social) students at SMA Deli Murni Bandar Baru. Sampling uses random sampling which is the method used to take samples. Information on student learning achievement was obtained from documents, while information on the home and school environment was obtained from distributing questionnaires. Estimated coefficient of determination (KD) was used to assess the data and evaluate it using Pearson product moment correlation calculations. Based on the findings of the Pearson product moment correlation calculation, a correlation of 0.468 was obtained for the family environment variable (X1) and a significance level of 0.05 for the school environment variable (X2) on student learning achievement in accounting subjects. Pay attention to the findings of the coefficient of determination for the family environment (21.9%) and the school environment (34.9%) to find out the influence. The findings of the statistical hypothesis test using the t test at a significance level of 0.05 show that the home and school environment significantly improves student learning achievement in accounting courses. Based on research findings, student learning achievement is positively influenced by the home and school environment.